1987
DOI: 10.1152/ajprenal.1987.253.4.f702
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the transport function of uricase, an oxidative enzyme

Abstract: [2-14C]urate uptake was examined in proteoliposomes prepared with phosphatidylcholine and either pig liver uricase or albumin, and in protein-free liposomes. Urate uptake was only evident in proteoliposomes that contained active uricase. Uptakes were indistinguishable in the presence and absence of inwardly directed gradients of sodium, potassium, or choline chloride or outwardly directed hydroxyl gradients. Both urate and allantoin accumulated within proteoliposomes during urate uptake; however, [2-14C]allant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Since prior studies implied that there is some degree of homology between UAT and uricase [1,2,36,37,39,40,54], and oxonate which is a competitive inhibitor of uricase [20] blocked the reconstituted channel, a local block of homology to uricase was sought. As depicted in Fig.…”
Section: Identification Of Local Block Of Homology To Uricase Within Uatmentioning
confidence: 99%
See 1 more Smart Citation
“…Since prior studies implied that there is some degree of homology between UAT and uricase [1,2,36,37,39,40,54], and oxonate which is a competitive inhibitor of uricase [20] blocked the reconstituted channel, a local block of homology to uricase was sought. As depicted in Fig.…”
Section: Identification Of Local Block Of Homology To Uricase Within Uatmentioning
confidence: 99%
“…First, the renal electrogenic urate transporter displays some similarities to the enzyme uricase [1,2,36,37]. Second, hepatic uricase functions as a urate transporter when incorporated in proteoliposomes [54] and a highly selective urate channel when inserted in lipid bilayers [39]. Third, uratebinding protein affinity purified from rat renal cortical cell membranes on urate or xanthine agarose gels is highly immunoreactive to the polyclonal antibody to porcine uricase [37].…”
Section: Introductionmentioning
confidence: 99%
“…Although solely an oxidative enzyme within peroxisomes, hepatic uricase appeared to function as a urate transporter when incorporated into liposomes (20) and as a highly selective urate channel when inserted in lipid bilayers (21). Moreover, urate-binding proteins that were affinity-purified from rat renal cortical cell membranes were shown to be highly immunoreactive to a polyclonal antibody to affinity-purified porcine hepatic uricase (19).…”
mentioning
confidence: 99%
“…[33][34][35] Interestingly, recent studies revealed that UOx is a peroxisomal globular protein enclosing a tunnel, 35 which possesses a characteristic property as a transporter of uric acid across a biomembrane, implying that UOx is a membrane protein. [36][37][38][39] The present study is conducted to mimic the functions of UOx in the biomembrane by embedding UOx in an artificial bilayer membrane.…”
mentioning
confidence: 99%
“…UOx (0.83 µmol dm -3 ) and 10 mmol dm -3 MMP were dissolved in the suspension of PCOP liposomes, followed by agitating vigorously for 10 min to incorporate both UOx and MMP in the liposome. 37,38 An Au disk plate (0.88-cm diameter) was used as an electrode substrate. The Au disk was polished successively with alumina slurries of 1.0 and 0.3 µm, subjected to ultrasonication in deionized water for 30 min, soaked overnight in a piranha solution, 9,55 and then mounted in a Teflon electrode holder which restricted the exposed area to 0.27 cm 2 .…”
mentioning
confidence: 99%